Risk assessment of coal seam floor water burst based on improved vulnerability index method - Xuefei WU (Meikuang Anquan)
The coal seam floor water burst has an inevitable impact on the safety production of coal mines. To prevent the occurrence of coal seam floor water burst in advance, effective risk assessment of coal seam floor water burst before mining can provide safety assurance for coal mining to a certain extent. Due to the fact that the traditional vulnerability index method focuses on different concealed disaster-causing geological factors, it leads to the drawbacks of large differences in credibility and increasingly repetitive evaluation results, a vulnerability index method based on DS evidence theory is proposed for coal seam floor water burst risk assessment. This method takes the main controlling factors of coal seam floor water burst from the bottom plate of the mining face and the geological structure of water diversion as the research object. Firstly, the Dempster synthesis rule of DS evidence theory is used to quantify the credibility of the interpretation of water diversion geological structure in the mining face obtained under different detection methods. The quantified DS fusion value is used as the vulnerability index coefficient; next, use the analytic hierarchy process to calculate the weight of the main control factors for coal seam floor water burst from the bottom plate of the mining face before mining; finally, the vulnerability index is calculated by composite superposition of the main control factors of coal seam floor water burst from the bottom plate and considering the credibility of the interpretation of water conducting geological structures; taking 7 main controlling factors for coal seam floor water burst from the bottom plate of the 61304 working face in a certain mine in Ordos as examples, including the water richness of Ordovician limestone aquifer, water pressure of the aquifer, boundary of collapse columns, and distribution map of fault lines, the weight of each main controlling factor was obtained. After normalizing the weight of each main controlling factor, an added weight sum was used to obtain the vulnerability zoning map for coal seam floor water burst from the bottom plate of the 61304 working face before mining, and the risk of coal seam floor water burst from the bottom plate was evaluated. The research results have proven the scientificity and feasibility of the vulnerability index method based on the DS evidence theory, which has a reference and guiding role in preventing coal seam floor water burst from the bottom plate of the mining face before mining, and has certain practical significance.